Overview of TOMAS plasma diagnostics. (14th February 2023) - Kovtun, Yu.; Goriaev, A.; López-Rodríguez, D.; Dittrich, L.; Petersson, P.; Moon, S.; Wauters, T.; Crombé, K.; Möller, S.; Buermans, J.; Verstraeten, M.; Brezinsek, S.
Abstract: This paper presents an overview of the TOMAS plasma diagnostics. The Langmuir probe method is employed to measure electron temperature, density and floating potential distributions.Two triple probes (horizontal and vertical distributions) and a single probe (horizontal distribution) are used. The measured plasma parameters by the triple and single probes are compared. The ion and neutral atom flux and energy distribution is respectively characterized with a Residual Field Energy Analyzer and a Time-of-Flight Neutral Particle Analyzer. To determine the elemental/charge content of the plasma, the passive method of time-resolved optical emission spectroscopy is used. The time dependence of the integral flow of plasma emission from the discharge is registered by a photodetector. Using a filter allows the photodetector to measure spectral line intensities. To record a wide variety of plasma events several video diagnostics are used. It includes slow video cameras and one high-speed camera in the visible range including Hα .